PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT KANTOR DESA PULAU RAKYAT PEKAN KECAMATAN PULAU RAKYAT KABUPATEN ASAHAN - Muhammad Cahyadi Nasution; Muhammad Fahcrul Rozi; Ratna Sari Dewi (Jurnal Genta Mulia, 2024)
This research aims to determine; (1) the magnitude effects of public service quality to community satisfaction in Desa Pulau Rakyat Pekan; (2) the magnitude effects of discipline employees work to community satisfaction in Desa Pulau Rakyat Pekan; (3) the magnitude effects of public service quality and discipline employees work to community satisfaction in Desa Pulau Rakyat Pekan. This research is an ex-post facto research with quantitative approach. Subjects in this research were students of community who have interests in Desa Pulau Rakyat Pekan and 100 peoples were chosed to be the samples of this study. Methods of data collection using questionnaires and documentation. Testing instrument validity used Product Moment correlation and reliability testing used Alpha Cronbach's. The prerequisite analysis test consists of normality test, linearity test, and multicollinearity test. The hypothesis testing used the simple regression analysis and multiple regression analysis. The results this research showed that; (1) there is a positive and significant effects of public service quality to community satisfaction with rx1y = 0,596; r2 x1y = 0,355; tcount (at 7,341) > ttable (at 1,984) at significance level of 5%; and an effective contribution of 14,4%; (2) there is a positive and significant effects of discipline employees work to community satisfaction with rx2y = 0,704; r2 x2y = 0,495; tcount (at 9.810) > ttable (at 1,984) at significance level of 5%; and an effective contribution of 38,6%; (3) there is a positive and significant effects of public service quality and discipline employees work to community satisfaction with Ry(1,2) = 0,728; R2 y(1,2) = 0,529; Fcount (at 54,547) > Ftable (at 3,090) at significance level of 5%; and an effective contribution of 52,9%.